Factors affecting the cleavage efficiency of the CRISPR-Cas9 system - Won Jun Jung; Soo-Ji Park; Seongkwang Cha; Kyoungmi Kim (Animal Cells and Systems)
The CRISPR-Cas system stands out as a promising genome editing tool due to its cost-effectiveness and time efficiency compared to other methods. This system has tremendous potential for treating various diseases, including genetic disorders and cancer, and promotes therapeutic research for a wide range of genetic diseases. Additionally, the CRISPR-Cas system simplifies the generation of animal models, offering a more accessible alternative to traditional methods. The CRISPR-Cas9 system can be used to cleave target DNA strands that need to be corrected, causing double-strand breaks (DSBs). DNA with DSBs can then be recovered by the DNA repair pathway that the CRISPR-Cas9 system uses to edit target gene sequences. High cleavage efficiency of the CRISPR-Cas9 system is thus imperative for effective gene editing. Herein, we explore several factors affecting the cleavage efficiency of the CRISPR-Cas9 system. These factors include the GC content of the protospacer-adjacent motif (PAM) proximal and distal regions, single-guide RNA (sgRNA) properties, and chromatin state. These considerations contribute to the efficiency of genome editing.